Voltage-dependent inactivation gating at the selectivity filter of the MthK K(+) channel - Thomson, Andrew S. (The Rockefeller University Press, 2010)
Voltage-dependent K(+) channels can undergo a gating process known as C-type inactivation, which involves entry into a nonconducting state through conformational changes near the channel’s selectivity filter. C-type inactivation may involve movements of transmembrane voltage sensor domains, although the mechanisms underlying this form of inactivation may be heterogeneous and are often unclear. Here, we report on a form of voltage-dependent inactivation gating observed in MthK, a prokaryotic K(+) channel that lacks a canonical voltage sensor and may thus provide a reduced system to inform on mechanism. In single-channel recordings, we observe that Po decreases with depolarization, with a half-maximal voltage of 96 ± 3 mV. This gating is kinetically distinct from blockade by internal Ca(2+) or Ba(2+), suggesting that it may arise from an intrinsic inactivation mechanism. Inactivation gating was shifted toward more positive voltages by increasing external [K(+)] (47 mV per 10-fold increase in [K(+)]), suggesting that K(+) binding at the extracellular side of the channel stabilizes the open-conductive state. The open-conductive state was stabilized by other external cations, and selectivity of the stabilizing site followed the sequence: K(+) ≈ Rb(+) > Cs(+) > Na(+) > Li(+) ≈ NMG(+). Selectivity of the stabilizing site is weaker than that of sites that determine permeability of these ions, suggesting that the site may lie toward the external end of the MthK selectivity filter. We could describe MthK gating over a wide range of positive voltages and external [K(+)] using kinetic schemes in which the open-conductive state is stabilized by K(+) binding to a site that is not deep within the electric field, with the voltage dependence of inactivation arising from both voltage-dependent K(+) dissociation and transitions between nonconducting (inactivated) states. These results provide a quantitative working hypothesis for voltage-dependent, K(+)-sensitive inactivation gating, a property that may be common to other K(+) channels.